PKM Penerapan Sistem Informasi Administrasi Kependudukan di Kantor Desa Koting C - Kristina Sujila; Marselus Don Bosko (Lembaga Pengembangan Kinerja Dosen, 2025)
Village Information System is an innovative solution to optimize village data management and accelerate access to information for the community. Population administration is an important aspect in the implementation of village government which functions to record and manage population data systematically. Koting C Village Office has implemented a computer-based population administration information system to improve the efficiency and accuracy of services. This system aims to accelerate the administration process, reduce recording errors, and facilitate access to population information. However, in its implementation there are still several obstacles that need to be fixed so that the system can run more optimally. This study was conducted in the context of Community Service (PKM) to analyze the implementation of the population administration information system at the Koting C Village Office, identify the obstacles faced, and find solutions to increase the effectiveness of this system. The methods used in this study include direct observation, interviews with village officials, and analysis of the population administration service process. The results of the study indicate that although the population administration information system has been implemented, there are still several obstacles that hinder its effectiveness. One of the main obstacles is the absence of a search feature based on name, Population Identification Number (NIK), or other keywords, so that village officials have to search for data manually, which slows down the service process.